ANALYSIS OF THE APPLICATION OF PATIENT SAFETY CULTURE IN PRABUMULIH CITY HOSPITAL, SOUTH SUMATERA, INDONESIA - Pitri Noviadi; Sulastri Sulastri (Lafadz Jaya Publisher, 2022)
Prabumulih City Hospital Accreditation graduation predicate in 2019 which decreased from fully accredited to mid-accredited, where one of the working groups that had not passed was the facility management and safety working group with a score of 67.62. This is also supported by data from the results of recording patient safety incidents for 3 consecutive years from 2018 to 2020. Departing from this problem, the authors are interested in conducting research on